استخدام طريقة الأغنية فى استيعاب المفردات بمدرسة المعهد الإسلامى مشارق الأنوار للبنات بباكن شوارنجين شربون - Faliqul Isbah (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2020)
Learning Arabic will not be sparated from the vocabulary, therefore we need a variety of methods and media that can facilitate the process of learning vocabulary. Especially for Islamic boarding schools which in their learning activites around Arabic texts, of course we need media that can help students so that mastery of the vocabulary can have a positive impact. Besides that in general for the linguist the more he knows vocabulary it is known that he is an expert in language. One of the media that can be used is song, because song ca increase morale, make things comfortable an easy to memorize. The use of this media by replacing the lyrics of the original song is changed with words related to modern educational vocabulary. The use of song media has a signficat influence on students ability to master vocabulary especially knowing meaning and as well pronouncing it. But the song media also has disadvantages incluiding not all vocabulary  can be taught with songs and not all the teachers are able to use it specially for those who cannot sing.